Razumeti ustavo - Kristan, Andrej (Revus (Ljubljana), 2014)
The author makes a claim in favour of distinguishing three ways of a constitution. He rejects first the (mis)use of the argument from intent as a rhetorical figure with no grounds to connect an interpretation of a constitutional text with the legitimacy of the historical text-writer. The author then supports his claim by introducing a thought experiment, according to which constitutional theory needs to distinguish clearly between the textual constitution, the ideologic constitutions, and the social constitution, being all in force at the same time.
Keywords: argumenta namena; besedilna ustava; družbena ustava; razlaga ustave; ustave